The conservation of old shophouses in Kampar and economics relation due to the new development of Bandar Baru Kampar / Nor Aini Mahyidin - Mahyidin, Nor Aini (2011)
This study concerns with the poor condition of the old shophouses in the old town in Kampar. The main issue to be pointed is the lack of awareness and expertise regarding the significance of the old shophouses as one of the main contribution to Kampar urban heritage, among both the local authorities and the owners. With the shophouses around Kuala Lumpur, Malacca and Penang now given a fully concern by the local authority and any others heritage agency such as Badan Warisan Negara and the Ministry Of Information Communication and Culture, but the situation are different in other towns like Kampar, where the awareness among the local authority and the owner are still low. Some of the old shophouses have been subjected to either changes or neglect that damage the essence of the old shophouses. With the development of new town, Bandar Baru Kampar - 5 kilometres from the old town, that supposed to be the interrelation town to old Kampar, suddenly became the threat to it. Since the opening of Bandar Baru Kampar the business run in the old town going slowly unbeneficial.